Specific Commercial Power of Attorney – Definition in Legislation of the Republic of North Macedonia - Petkukjeski, Ljupco; Andonov, Marko; Radenkov, Ljubomir (International Finance and Banking, 2024)
The aim of this paper is to give a substantive definition of the procuration as the broadest commercial power of attorney in accordance with the legislation of the Republic of Northern Macedonia and as a special type of power of attorney which can be given only by the person who has the role of a merchant, to indicate the legal nature of the procuration, its meaning, authorization and restriction in the trade, in the relations that occur between the represented and the procurator, the procurator ant the third party, the responsibility, its strengths and weaknesses and similar.